Institutions, Trade Union Effectiveness, and Workers' Bargaining Power: A Comparative Study of Indonesia and Germany - Neysa Adelia Nova Abdullah Putri; Rachmad Kresna Sakti; Nugroho Suryo Bintoro (Indonesian Journal of Taxation and Accounting, 2026)
Purpose - This study examines how institutional design shapes the effectiveness of trade unions in strengthening workers' bargaining power. It compares Germany and Indonesia to explain why similar union presence can produce different bargaining outcomes. Methods - This study uses a qualitative comparative design based on secondary data from peer-reviewed journals, institutional reports, and labour regulations. The sources were selected through a structured literature search and analysed using thematic content analysis and a comparative institutional matrix. Findings - The findings show that union effectiveness is shaped less by membership numbers alone than by institutional access, legal recognition, collective bargaining coverage, and formal participation in decision-making. Germany's codetermination, works councils, and sectoral bargaining embed unions in industrial governance. Indonesia's fragmented unions, weak enforcement, limited bargaining coverage, and high informality reduce the practical influence of unions. Research Implications - The study implies that strengthening workers' bargaining power requires institutional reform, not only recruitment of union members. Its limitation is that it relies on secondary qualitative sources and does not statistically test causal relationships across countries. Originality - This study contributes to comparative industrial relations by positioning institutional embeddedness as the key mechanism linking trade union effectiveness to workers' bargaining power in coordinated and fragmented labour regimes.